Sustainability assessment atlas: innovation on decision-making support systems for sugarcane sector in São Paulo State - Mendizábal Cortés, Alejandra Daniela (2017)
The sugarcane cultivation in Brazil is one of the leading economic pillars, as it is an ethanol precursor, a renewable fuel produced in industrial markets as a substitute for fossil fuels. Brazil produces about 27.44% and 43% of the world production of ethanol and sugar, respectively. São Paulo state has the environmental and logistic conditions for a sugarcane industry, both characteristics turn it the main Brazilian\'s sugarcane production pole, with 63.74% of sugar and 48.23% of ethanol production (RFA, 2017). In São Paulo, the Agro-Environmental Zoning establishes the areas to cultivate sugarcane. However, tools to check the sugarcane industry influences on municipalities\' socioeconomic aspects are superficial. Considering sugarcane industry importance to São Paulo state and Brazil, the Nucleus of Research and Extension on Sustainability and Sanitation initiated different investigations and efforts to study, analyze, and predict the sugarcane industry\'s impacts and sustainability. Within this research\'s general line, the focused was on environmental impacts with emphasis on their accumulation and synergy, climate change scenarios, sustainability concept management among its stakeholders, industry\'s governance, mill unit\'s sustainability evaluation, and so forth. In this context, it appears as a necessary and conclusive step the sustainability assessment tool\'s development, allowing sugarcane industry evaluation, while respecting the individual circumstances. Therefore, this project objective is to develop a sustainability assessment model to sugarcane sector decision-making implemented in an atlas format. The sustainability assessment model includes eighteen indicators about environmental, social, economic, and municipal policies issues. Those indicators describe seven of the eight Gibson\'s principles. It was the principles grouped according to their indicators\' nature in three domains (environmental, socioeconomic, and municipal policies) that finally compose the sustainability index. Some indicators are considered elimination factors to avoid the trade-off between principles and domains, because more than limiting the calculus\' next level, they cut the unsustainable situations by classifying them as such. In the end, the atlas present twelve maps that describe the distribution of principles, domains, and sustainability index across São Paulo state. The results show that the sugarcane ethanol sector still faces new environmental and social impacts, while the Agro-environmental Zoning presents a limited contribution to sustainability. According to the model, environmental issues (Domain A) there are new areas where sugarcane must be forbidden or, at least, increase its requirement for water quality improvement. Nevertheless, half of the state of São Paulo has the environmental condition for sugarcane cultivars. For socioeconomic issues (Domain B), most municipalities presented a moderate performance. In the Domain C few municipalities reached the very high-performance, while the high-performance stood out for being the main one. In both, the Domain B and the Domain C, moderate and high are the significant municipalities\' performances. The atlas format results in a useful instrument, because it is easy to understand, can deliver a full state context and regions contrast, as well it brings a specific outcome for each municipality, and in case of environmental issues it also presents more precise details according to natural limits. Finally, the sensitivity analysis showed that the social indicators explain the results in 19.2%, while the municipal policy indicators influence 15.7% and the economic indicators 5.7%. The environmental indicators correspond to 59.4%, with indicator A3 (water quality) accounting for 19.7%.